Pemikiran Psikologis dan Terapinya Menurut Abubakr Muhammad Ibn Zakariyya Al-Razi (854-925 M) - Pamukti, Aryani; Soleh, Achmad Khudori (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
The psychological thoughts of Abubakr Muhammad ibn Zakariyya Al - Razi (854-925 AD) were very important in the development of psychology because Al - Razi (854-925 AD) made an important contribution to understanding the relationship between physical, emotional, mental, and spiritual in humans. Al - Razi (854-925 AD) developed a theory about human personality and temperament and identified environmental factors that influence human development. This study aims to reveal the thoughts of Al - Razi (854-925 AD) about human personality and environmental factors that influence human development, as well as the psychological therapies that are developed. The method in this study is a qualitative method using library research, while the object of this study is psychological thinking from the perspective of Abubakr Muhammad ibn Zakariyya Al - Razi (854-925 AD). Al - Razi's thought (854-925 AD) showed that (1) Al - Razi revealed that human personality consists of four elements: blood, mucus, yellow bile, and black bile. (2) Al - Razi emphasized the importance of seeing human beings as complex beings and that human physical and mental health are interrelated and influence one another. His thoughts and research are very relevant and useful for the development of psychology. (3) In the view of Al - Razi (854-925 AD), holistic and integrated treatment and therapy is the key to achieving optimal mental health. Al - Razi developed various kinds of therapy, including pharmacotherapy, physical therapy, psychological therapy, and spiritual healing.